Surface behavior of low-temperature molten salt mixtures during the transition from liquid to solid - Bhuin, Radha Gobinda; Schreiber, Patrick; Heller, Bettina; Scheuermeyer, Marlene; Wasserscheid, Peter; Steinrück, Hans-Peter; Maier, Florian (Journal of Molecular Liquids, 2019)
We report on surface investigations of cesium and tetraphenylphosphonium bis(trifluoromethylsulfonyl)imide (Cs[Tf2N], [PPh4][Tf2N]) molten salts and their mixtures. Depending on composition, these ionic compounds combine low melting points with exceptionally high thermal stability, and thus, exhibit considerably enlarged thermal operation windows compared to conventional ionic liquids. To elucidate their liquid-solid transition behavior in the near-surface region, temperature-dependent angle-resolved X-ray photoelectron spectroscopy (ARXPS) investigations were performed using our unique laboratory electron spectrometer DASSA ("Dual Analyzer System for Surface Analysis"), dedicated for investigations of macroscopic liquid samples. We followed temperature-induced changes in bulk and surface composition within the first nanometers of the neat salt melts and of Cs[Tf2N]: (PPh4][Tf2N]= 3 : 1 and 1 : 3 mixtures. In the mixtures, pronounced surface enrichment of Cs+ on expense of the bulky [PPne ions was found in the liquid state at temperatures close to the liquid-solid transition. In the solid state of Cs[Tf2N]-rich mixtures, [PPH4](+) completely vanishes from the near-surface region probed by XPS. (C) 2018 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license.
CRIS-Team WoS Importer:2019-02-27